The Framework for Resilient Industry A Holistic Approach for Developing Economies - Kumar, Narinder (Emerald Studies in Finance, Insurance, and Risk Management Series, 2024)
The Framework for Resilient Industryexamines the historical background, current status, and future opportunities and challenges of the Indian industry, delving into region-specific issues such as micro, small, and medium enterprises (MSMEs), economic policy, risk management and sustainable industries